Functional characterization of a predicted i-type lysozyme-like effector from Meloidogyne incognita that contributes to nematode fecundity in rice - Vũ Phong Nguyễn; Anne-Sophie Petitot; Karine Lambou; Pascal Gantet; Stéphane Bellafiore; Diana Fernandez (Physiological and Molecular Plant Pathology, 2026)

Two Lateral Organ Boundary Domain Transcription Factors HvCRL1 and HvCRL1L1 Regulate Shoot-Borne Root Formation in Barley (Hordeum vulgare L.) - Thu Dieu Nguyen; Mathieu Gonin; Michal Motyka; Antony Champion; Goetz Hensel; Pascal Gantet; Véronique Bergougnoux (Journal of Plant Growth Regulation, 2025)
Plant-specific LOB-domain (LBD) transcription factors are crucial in post-embryonic root initiation. In cereals, the fibrous root system comprises primary and seminal roots that develop during embryogenesis and lateral- and crown roots that develop post-embryonically from root or stem, respectively. In rice, the CROWNROOTLESS1 (CRL1) LBD transcription factor is the core regulator of crown root initiation and a direct target of the auxin response factor (ARF)-mediated auxin signaling pathway. Orthologs of CRL1 have been identified and characterized in several species, where their role in crown root initiation has been validated. In barley, we identified two genes phylogenetically closely related to the rice CRL1 genes that we named HvCRL1 and HvCRL1L1 . Using a crown root inducible system (CRIS), we identified that both HvCRL1 and HvCRL1L1 are expressed in response to auxin during the early steps of crown root differentiation in stem base, with HvCRL1 transcripts being accumulated quickly during the first hour of treatment. Transient activation assays in rice protoplast showed that HvCRL1 could bind the LBD-box , a consensus DNA sequence recognized by LBD transcription factors, whereas HvCRL1L1 did not. Both genes can partially complement the crl1 rice mutant. Loss-of-function mutation in each gene drastically impairs crown root formation in barley. These data show that HvCRL1 and HvCRL1L1 are both involved in the regulation of crown root formation in barley but that these two transcription factors likely act through distinct and complementary pathways in this developmental process.

Multiple layers of regulators emerge in the network controlling lateral root organogenesis - Antoine Beckers; Akihito Mamiya; Masahiko Furutani; Malcolm J. Bennett; Hidehiro Fukaki; Shinichiro Sawa; Pascal Gantet; Laurent Laplaze; Soazig Guyomarc’h (Trends in Plant Science, 2025)

p2 of Rice grassy stunt virus (RGSV) and p6 and p9 of Rice ragged stunt virus (RRSV) isolates from Vietnam exert suppressor activity on the RNA silencing pathway - Thanh Duc Nguyen; Séverine Lacombe; Martine Bangratz; Hoang Anh Ta; Do Nang Vinh; Pascal Gantet; Christophe Brugidou (Virus Genes, 2015)

The mariner Mos1 transposase produced in tobacco is active in vitro - Xavier Thomas; Sabah Hedhili; Laurent Beuf; Marie-Véronique Demattéi; Hélène Laparra; Giang Ngan Khong; Jean-Christophe Breitler; Frédéric Montandon; Elodie Carnus; Frédéric Norre; Daniel Burtin; Pascal Gantet; et al. (Genetica, 2010)

Regulation of the terpene moiety biosynthesis of Catharanthus roseus terpene indole alkaloids - Sabah Hedhili; Vincent Courdavault; Nathalie Giglioli-Guivarc’h; Pascal Gantet (Phytochemistry Reviews, 2007)

CaaX-prenyltransferases are essential for expression of genes involvedin the early stages of monoterpenoid biosynthetic pathwayin Catharanthus roseus cells - Vincent Courdavault; Martine Thiersault; Martine Courtois; Pascal Gantet; Audrey Oudin; Pierre Doireau; Benoit St-Pierre; Nathalie Giglioli-Guivarc’h (Plant Molecular Biology, 2005)

Catharanthus roseus G-box binding factors 1 and 2 act as repressors of strictosidine synthase gene expression in cell cultures - Yann Sibéril; Sandrine Benhamron; Johan Memelink; Nathalie Giglioli-Guivarc'h; Martine Thiersault; Bertrand Boisson; Pierre Doireau; Pascal Gantet (Plant Molecular Biology, 2001)